Clima urbano: interfaces termodinâmicas e hidrodinâmicas no contexto socioambiental de Feira de Santana-BA - Silva, Michelle Pereira da Costa da (2023)
Urbanization has underscored the need to consider it as an integral part of environmental dynamics, as the transformations resulting from this process bring about modifications and introduce new characteristics to biophysical components. Given this reflection, the interfaces between hydrodynamic and thermodynamic processes are considered as subsystems of urban climate. In this context, the municipality of Feira de Santana, Bahia, stands out due to its expanding urban space and significant alterations in the landscape, which create a favorable environment for the development of its unique climate. The specific objectives are as follows: to characterize the geoecological aspects, with an emphasis on climatic behavior; to identify the morphology and geourban attributes of the landscape; to evaluate the thermal and hydrodynamic subsystems; and to define the type and seasonal pattern of socio-environmental implications of hydrodynamic processes. To achieve these goals, systemic relationships call for a geographical approach, which enables the connection of socio-environmental causes and effects, using the landscape as a category of analysis, based on the Urban Climate System (SCU). The methodology comprises a set of procedures, qualitative and quantitative attributes, organized into the following dimensions: climate, metabolism, and urban morphology, biohydroclimatic regularization, and hydrodynamic impacts. The study presents the amplitude, asymmetry, and dispersion of rainfall on both a monthly and annual scale, demonstrating that the months with the greatest variability occur at the beginning of summer and autumn. It is during this seasonal period that the largest number of journalistic records related to the hydrodynamic field was identified in the time scale spanning from 1990 to 2021. Neighborhoods such as Campo Limpo, Queimadinha, and George Américo have historically contended with issues of flooding and/or inundations. Conversely, the thermodynamic field has exhibited an increase in thermal amplitude, giving rise to heat islands. This is a consequence of the reduction in vegetated areas and an increase in impermeable surfaces. Itinerant measurements along transects indicate temperature and air humidity conditions as a function of geourban characteristics. Thermal differences delineate extremes of heat island formation and areas where temperatures are mitigated. The potential of ponds and green areas to mitigate temperature and increase humidity is confirmed. In summary, the expansion of the urban area represents not only the production of space driven by strategic interests such as real estate speculation but also a scenario susceptible to omissions, particularly concerning local structural problems that permeate the urban fabric, exacerbating urban socio-environmental vulnerabilities.